Experimental Study of the Effect by Double-Stage Throttling on the Pressure Relief Characteristics of a Large-Scale CO2 Transportation Pipeline - Huifang Song; Tingyi Wang; Jingjing Qi; Kai Jin; Jia Liu; Feng Li; Fanfan Qiao; Kun Zhao; Baoying Yin; Jianliang Yu (Energies, 2025)
The safety of pipeline transportation technology is the key to guaranteeing the development and application of CCUS. In the process of CO2 pipeline transportation, manual pressure relief may be required due to equipment failure, overpressure, or other reasons. However, the sharp temperature drop in the evacuation process may lead to the formation of dry ice, which may cause a pipeline blockage and equipment damage. Although the multi-stage throttling method of pressure relief can effectively control the stability of the equipment, the effect on the low temperature of the pipeline needs to be further investigated. Therefore, in order to evaluate the safety of multi-stage throttling pressure relief, a comparative experiment of dense-phase venting with double-stage throttling was carried out based on an industrial-scale pipeline experimental device. The results show that the double-stage throttling pressure relief scheme can significantly reduce the pressure drop rate and improve the stability of the pressure relief structure. Moreover, the temperature drop limit upstream of the main pipeline is controlled under the double-stage throttling scheme, but it exacerbates the low temperature level downstream, which is not conducive to mitigating the risk of freeze-plugging of the pressure relief valve. Therefore, it is recommended that the double-stage throttling relief scheme be used to close the valve in time to return to the temperature and to adopt an intermittent means of pressure relief.